2022
DOI: 10.3389/fitd.2022.963674
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-M. leprae antibodies in healthy children in China: A systematic review of Chinese literature

Abstract: Leprosy is an infectious disease caused by Mycobacterium leprae (M. leprae) that mainly involves the skin and peripheral nerves, causing lifelong deformities and social stigma. As evident from the practically stable number of new cases reported worldwide during the past decade, transmission is still ongoing. On route to leprosy elimination, an appropriate tool is needed to monitor M. leprae transmission. M. leprae-specific antibodies indicate infection with M. leprae, but do not differentiate between present a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Screening for quantitative assessment of anti-PGL-I IgM levels in children identified 11.58% seropositivity in 12 villages in Bihar, India. These data are in line with seroprevalence data reported ( 20 , 21 ) for other endemic areas without PEP in the past decades. There was a slight, significant increase with age, but no difference in seropositivity between genders was observed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Screening for quantitative assessment of anti-PGL-I IgM levels in children identified 11.58% seropositivity in 12 villages in Bihar, India. These data are in line with seroprevalence data reported ( 20 , 21 ) for other endemic areas without PEP in the past decades. There was a slight, significant increase with age, but no difference in seropositivity between genders was observed.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, cutoff values were often chosen arbitrarily. However, analysis of data available from China showed that if the same method was used, a decrease in disease prevalence or new case detection rate corresponded to a decrease in anti- M. leprae antibody seroprevalence in children ( 21 ), adding the potential of measuring antibodies in children as a tool for recent transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation